Bibliometric analysis of publication trends of bullying interventions in preschool age children - Hidayati, Eni; Fitrikasari, Alifiati; Sakti, Hastaning; Dewi, Setiawati (University of Muhammadiyah Semarang, 2024)
Research on bullying in preschool children is a topic that is often carried out by researchers which is presented in bibliometric results using the Publish or Perish and VOSviewer applications. This study aims to find research on bullying interventions for preschool children. This research uses a bibliometric application using data from Google Scholar and Crossref to produce articles about bullying against young children from 2019-2023. This research shows that from 994 papers published from 2019 to 2023, 5 clusters were found with 35 items that appeared in almost the same terms related to bullying interventions in preschool children. Further recommendations from the results of this research analyze the development of bullying interventions in preventive programs for preschool-aged children that can work together with schools, families and interactions between children, especially in Indonesia.